TINJAUAN KOMPREHENSIF TENTANG TINGKAT SUKU BUNGA, FLUKTUASI KURS RUPIAH PER DOLLAR AS DAN RETURN SAHAM - Jeanne Asteria W (UMSurabaya Publishing, 2008)
The objective of this paper is to explain that monetary condition is very closely related with the interest rate, value of foreign exchange and the performance of investment at Capital Market, especially the economic systems of developing countries like Indonesia, the role of Government Bank is very important to keep maintain the value of foreign exchange. Investor always wait and see before making decision to buy, sell or hold the stocks & all of the action depent on monetary situation, because they expect high return. Indonesian Government can create good condition in social and economic which means growth economic. Key Word: Interest Rate, Value of Foreign Exchange, Return of Capital Stock